2014
DOI: 10.1186/1479-5868-11-32
|View full text |Cite
|
Sign up to set email alerts
|

Parental safety concerns and active school commute: correlates across multiple domains in the home-to-school journey

Abstract: BackgroundEmpirical evidence of the relationship between safety concerns and walking to school (WTS) is growing. However, current research offers limited understanding of the multiple domains of parental safety concerns and the specific mechanisms through which parents articulate safety concerns about WTS. A more detailed understanding is needed to inform environmental and policy interventions. This study examined the relationships between both traffic safety and personal safety concerns and WTS in the U.S.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 41 publications
5
52
1
1
Order By: Relevance
“…Half of the studies were from North America (12 from the USA, one from Canada) [31][32][33][34][35][36][37][38][39][40][41][42][43], four were from Australia [44][45][46][47], three from the Netherlands [48][49][50], two from Belgium [51, 52•] and one each from the UK [53•], Portugal [54], Spain [55] and Norway [56]. The majority of the studies (n=22) included crosssectional analyses only; four studies included a prospective design [33, 48, 49, 53•] and two included both crosssectional and prospective analyses [33,48].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Half of the studies were from North America (12 from the USA, one from Canada) [31][32][33][34][35][36][37][38][39][40][41][42][43], four were from Australia [44][45][46][47], three from the Netherlands [48][49][50], two from Belgium [51, 52•] and one each from the UK [53•], Portugal [54], Spain [55] and Norway [56]. The majority of the studies (n=22) included crosssectional analyses only; four studies included a prospective design [33, 48, 49, 53•] and two included both crosssectional and prospective analyses [33,48].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies specifically included attributes of the school neighbourhood [38,39,42,47], and four examined route characteristics (three to school and one towards the nearest non-residential destination) [31, 32, 38, 53•]. All studies included at least one attribute related to the built environment; however, only 16 studies included attributes related to the social environment [32-35, 38, 40, 43-46, 48-50, 52•, 53•, 54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their studies found that the closer the distance between school and home, the higher the perception of safety among parents. Other factors such as the security system in school, the type of development surrounding the school and the school condition also influence the perceived safety of children among parents (Mammen, Buliung & Lay, 2012;Oluyomi et al, 2014). McDonald (2008) suggests that a typical walking rate for school-aged children is about 2.7 miles per hour (or 1.35 miles per 30 minuteperiod).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Public areas are areas that include residential area, schools, parks, shopping malls and other public places. According to Mammen, Buliung & Lay (2012) and Oluyomi et al (2014), distance is one of the factors that influences the element of safety among children. Their studies found that the closer the distance between school and home, the higher the perception of safety among parents.…”
Section: Background Of the Studymentioning
confidence: 99%